Detection of Aeromonas hydrophila proteins immunogenic in rabbit - Maji, S; Mali, P; Joardar, S N (The Indian Journal of Animal Sciences, 2011)
Isolates (12) of Aeromonas hydrophila were generated from haemorrhagic ulcerative lesi ons of goldfish, Carassius auratus L. Soluble protein antigen was prepared from one representative strain, A. hydrophila GFU 10 and was subsequently subjected to SOS-PAGE analysis. It revealed 19 polypeptide bands in the range of 19 kOa to 111 kDa. seroreactivity of the antigen was assessed in agar gel precipitation test (AGPT) and counter current immunoelectrophoresis (CIE) using hyperimmune serum raised in rabbit. Westernblot analysis showed that the antigen of the strain contained three immunogenic polypeptides of approximate molecular weight 57,23 and 21 kDa indicating their serodiagnostic potentiality.